Tuberculosis's cargoman: bacteria load RNA into host extracellular vesicles - Biton, Mirit (EMBO Rep, 2019)
Tuberculosis remains one of the deadliest infectious diseases worldwide. Mycobacterium tuberculosis (M.tb) has developed various mechanisms to manipulate the human host, in particular by disrupting the host phagosome and the immune response. It is becoming evident that secreted extracellular vesicles (EVs) are involved in the dynamic crosstalk between M.tb and the host cells. These vesicles shuttle different cargo components, such as RNA, lipids, and proteins, between cells. In this issue of EMBO Reports, Cheng and Schorey 1 describe a previously unknown EV‐mediated process, regulating M.tb RNA loading into EVs and their internalization by naïve macrophages. They identify the mycobacterial Sec2 secretion system as involved in RNA loading into EVs and show that secreted vesicles contain bacterial RNA that not only promotes IFN‐β production upon entry into target cells, but also leads to M.tb clearance via the activation of the host's RIG‐I/MAVS signaling pathway. Importantly, combined treatment with secreted EVs and antibiotics decreases bacterial load in a mouse model, improving lung pathology compared to treatment with antibiotics alone.